Critical Discourse Analysis of the Role of Mass Media in the Cancellation Policy of Hajj Pilgrims during the Pandemic - Rohmanur Aziz (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
This study aims to reveal the role of the media in disseminating information regarding the cancellation of the departure of pilgrims from the critical discourse dimensions. Therefore, this research method uses Critical Discourse Analysis from Norman Fairclough. The results of this study indicate that the role of the media in the cancellation policy of Hajj pilgrims in 2021 consists of three essential things. First, the media sided with the news content about the cancellation of the hajj based on norms by the law and various derivative regulations. Second, the mainstream media group has its concept in understanding how to disseminate the information so that it can become a public discourse and understand the public after being back on the mainstream media stage. Third, the media behaves like a ‘pendulum’ that can go back and forth to contribute to "orchestrating" the public discourse in this context regarding the cancellation of the departure of the pilgrims.Penelitian ini bertujuan untuk mengungkap peranan media dalam menyebarluaskan informasi mengenai pembatalan keberangkatan jamaah haji dilihat dari dimensi-dimensi wacana kritis. Oleh karena itu metode penelitian ini menggunakan Analisis Wacana Kritis dari Norman Fairclough. Hasil penelitian ini menunjukkan bahwa peranan media dalam kebijakan pembatalan jemaah haji tahun 2021 terdiri dari tiga hal penting. Pertama, media berpihak pada konten pemberitaan tentang pembatalan haji berdasarkan pada norma yang sesuai dengan undang-undang dan berbagai peraturan turunannya. Kedua, kelompok media arus utama memiliki konsep tersendiri dalam memahami cara menyebarluaskan informasi sehingga dapat menjadi wacana publik, namun sekaligus dapat memahamkan publik setelah kembali dimainkan di panggung media arus utama. Ketiga, media berperilaku sebagai bandul pendulum yang dapat bolak-balik berkontribusi dalam “mengorkestrakan” wacana publik dalam konteks ini tentang pembatalan pemberangkatan jemaah haji.